Stability Evaluation of Rock Pillar Between Twin Tunnels Using Numerical Modelling - Kalouni, Suresh Raj; Kalouni, Harendra Raj (KTFT Journal, 2024)
The stability of rock pillars between twin tunnels is a critical aspect of tunnel design and construction. To ensure the stability of rock pillars between twin tunnels, this study employ numerical modeling to assess pillar stability based on excavation method, tunnel geometry, determine pillar length based on rock mass quality, and quantify deformation, stress, and zone of influence of twin tunnels. To explore the role of rock mass quality in influencing pillar stability, the study considers factors such as rock strength, intactness, and discontinuity characteristics. Numerical modeling simulates the excavation process, considering the effects of rock mass properties, in situ stress conditions, and excavation methods. The results of the numerical simulations provide valuable insights for optimizing rock pillar design and construction practices for twin tunnels.